The activity of lung irritant receptors during pneumothorax, hyperpnoea and pulmonary vascular congestion - Sellick, Hilary (1969)
1. The activity of lung irritant receptors during pneumothorax, hyperpnoea and pulmonary congestion has been studied by recording from single vagal nerve fibres from the receptors in rabbits. 2. The receptors were stimulated during induction and during removal of pneumothorax. 3. Pneumothorax caused a greater depression of minute volume in bilaterally vagotomized rabbits, compared with those with intact vagus nerves. 4. Hyperpnoea due to breathing through an added dead space increased the discharge of the receptors. Experiments on paralysed and artificially ventilated rabbits showed that this was not a direct action of the asphyxial changes in blood gas tensions. 5. Pulmonary congestion, induced by inflating a balloon in the left atrium, stimulated the receptors in paralysed artificially ventilated rabbits. 6. The evidence that the receptors cause vagal reflex hyperpnoea and bronchoconstriction is discussed, together with their role in the reflex ventilatory and bronchomotor changes in the conditions studied.